2006
DOI: 10.4314/bcse.v20i1.21156
|View full text |Cite
|
Sign up to set email alerts
|

<b>INTERACTION OF 2-(2'-HYDROXY)PHENYLBENZOTHIAZOLINE WITH SOME METAL IONS: DETERMINATION OF ITS DISSOCIATION CONSTANT IN AQUO-ORGANIC MEDIA</b>

Abstract: Potentiometric titrations were carried out with 2-(2'-hydroxy)phenyl benzothiazoline (HPBT) in various 50%v/v aquo-organic media (dioxan-water, acetone-water, methanol-water, and ethanol-water) and in different percentages of dioxan. The results indicated that the ligand is a monoprotic acid with pKa corresponding to the hydroxyl group. The pKa value of HPBT determined in various aquo-organic media followed the regular order of the reciprocal of dielectric constant. The solid metal complexes employing HPBT wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The pH-metric titrations were carried out in 70% dioxan-water medium at 303 K and 0.1 M (KNO 3 ) ionic strength. The dissociation constant values were calculated using Irving-Rossotti titration technique [18][19][20][21][22][23][24][25]. From the titration data obtained, dissociation constants have been calculated from the linear plot of log (1n A )/ n A Vs pH (Fig 7).…”
Section: Equilibrium Studiesmentioning
confidence: 99%
“…The pH-metric titrations were carried out in 70% dioxan-water medium at 303 K and 0.1 M (KNO 3 ) ionic strength. The dissociation constant values were calculated using Irving-Rossotti titration technique [18][19][20][21][22][23][24][25]. From the titration data obtained, dissociation constants have been calculated from the linear plot of log (1n A )/ n A Vs pH (Fig 7).…”
Section: Equilibrium Studiesmentioning
confidence: 99%
“…22-25 A survey of literature reveals that aryl benzothiazolines when interact with metal ions to form solid complexes, various structural changes occur in ligands [14][15][16][17] . The studies on 2-(2'-hydroxy) phenyl benzothiazoline complexes revealed that in presence of Cu(II) metal ion the cleavage of thiazoline ring, subsequent schiff base formation through the transfer of proton from nitrogen to sulphur and then dissociation of same proton from sulphur and second proton from hydroxyl group of phenyl ring occurred enabling its copper complex formation [18] . In present study as the ring cleavage is hindered by acetyl group at ring nitrogen, in presence of metal ions under the conditions of metal complex formation, only one proton dissociation occurs and the benzothiazoline ring remain as such.…”
Section: Thermo Gravimetric Analysis Of Cu-ahpbt Cu-ahcpbt Cu-ahmpbmentioning
confidence: 99%
“…The pH-metric titrations were carried out in 70% dioxan-water medium at 303 K and 0.1 M (KNO 3 ) ionic strength. The dissociation constant values were calculated using Irving-Rossotti titration technique [18][19][20][21][22][23][24][25]. From the titration data obtained, dissociation constants have been calculated from the linear plot of log (1-n A )/ n A Vs pH (Fig 7).…”
Section: Equilibrium Studiesmentioning
confidence: 99%